Burden of Anemia: A profile of a tertiary care hospital - Joshi, Rinku; Bajracharya, S.; Gurung, S.; Shrestha, D.B. (Journal of Nepalgunj Medical College, 2018)
Introduction: Globally, anemia is the burning health problem with significant disability associated with it. Iron deficiency anemia (IDA) is the commonest cause of anemia more so in developing and underdeveloped part of world. Normocytic anemia is the common finding following microcytic hypochromic and macrocytic in peripheral blood film study. To understand more about the type of anemia among anemic patients in our setting this study was carried out. Objectives: This study aims to see the prevalence and aetiology of anemia among Nepal army personnel and their families in a Kathmandu based tertiary level hospital. Methods: This cross-sectional study was conducted over a six months period through June 30th to December 31st 2017 among 342 anemic patients presented to hematology clinic of Shree Birendra Hospital in Kathmandu with the help of data collection tool. Etiology of anemia was worked out. The study was conducted after approval from local IRC. Collected data were entered in SPSS version 22 and analyzed. Result: Mean hemoglobin value was 8.45±1.61 gm/dL and the mean age of the patient was 52.04±18.32 years. Among the patients of anemia, generalized weakness was the commonest (159, 46.5%) presenting complaint followed by per vaginal bleeding and upper gastrointestinal bleeding. Moderately severe anemia was the commonest (159, 46.5%) laboratory finding. In peripheral blood film study, microcytic hypochromic picture was the commonest finding (169, 49.4%) favoring commonest cause of anemia as iron deficiency followed by anemia of chronic disease.70 % of the participants were female. Conclusion: The study identified nonspecific complaints like generalized weakness as the predominant presenting complaints of anemia which is commonly neglected. Further, noninvasive tests like peripheral blood film are an important diagnostic tool which can guide us to the possible aetiology of anemia. This study showed iron deficiency anemia and anemia of chronic disease as important differential diagnosis of anemia in our context. This was a small scale study conducted to access the prevalence of anemia among Nepal army personnel and their families. Hence a larger multicentric study is needed to make it more applicable.